Developing teacher professionalism independently through the utilization of information technology media - Nor Maya; Dian Hidayati (Jurnal Penelitian Ilmu Pendidikan, 2024)
This study aims to describe the development of teacher professionalism at SMP Muhammadiyah 3 Balikpapan, carried out independently using information technology media. This study used a qualitative approach. Data collection methods included interviews and documentation. The analysis results consisted of five categories with various underlying indicators. The five categories were intrinsic motivation, extrinsic motivation, platforms followed, programs participated in, and training outcomes. The indicator of intrinsic motivation is the teacher as an educator, and the teacher must learn. The needles found in extrinsic motivation were upgrading knowledge, growing teaching abilities, increasing knowledge, and improving skills. For platforms followed, the indicators uncovered included Literacy Platform, Extensive Reading, Smart Teacher, E-Guru ID, E-Guru Digital, Chrome Book, Canva for Education, Asus for Education, and Merdeka Mengajar Platform. In addition, the indicators of the programs participated in revealed were making learning videos, learning media, teaching strategies, learning assessment applications, and learning administration. Finally, the needles from the training outcomes are missed teachers, interactive learning, fun lessons, exciting learning, and easy-to-understand lessons. In conclusion, the insights obtained from this study can inform teachers in maximizing teacher professionalism, which requires strong motivation from within the teacher who is aware that as educators, they must continue to learn to produce interactive, fun, and exciting learning so that the students in the classroom always await their presence. Teacher professionalism can be developed through various efforts, i.e., by participating in multiple trainings and webinars using information technology, which can be done online because they can better manage their time and choose the program/content they want to study.